Fluorescent ureteral catheters in laparoscopic surgery for rectal cancer with invasion of the uterus: A case report. (July 2022) - Kitagawa, Takahiro; Ryu, Shunjin; Okamoto, Atsuko; Marukuchi, Rui; Hara, Keigo; Ito, Ryusuke; Nakabayashi, Yukio
Abstract: Introduction: Resection of the uterus is required in some cases of colorectal cancer with invasion of the uterus. Localisation of the ureters to prevent ureteral injuries is important during resection of advanced colorectal cancer and combined resection of the uterus. Case presentation: We report a case of a woman in her 80s with rectal cancer with invasion of the uterus. She presented with appetite loss and lower abdominal pain. She was hospitalised after being diagnosed with intestinal obstruction due to rectal cancer. Colonoscopy revealed a tumor involving 100% of the circumference of the rectosigmoid colon, and imaging showed rectal cancer with invasion of the uterus and a giant uterine fibroid. Fluorescent ureteral catheters were placed bilaterally under cystoscopy, and laparoscopic anterior rectal resection, combined hysterectomy, and bilateral adnexectomy were performed 1 day later. Near-infrared visualisation of these catheters enabled safe release of the surrounding tissues from the uterus. Clinical discussion: Surgical treatment of rectal cancer with invasion of the uterus is not standardised and requires more complicated procedures, which are associated with a high risk of ureteral injury. Fluorescent ureteral catheters allow visualisation of the course of the ureters without releasing them, thereby enabling safe surgery. Conclusion: In fluorescence-guided surgery for rectal cancer, fluorescent ureteral catheters are particularly useful in patients with suspected invasion of other organs. Highlights: T4b rectal cancer has higher risk of ureteral injury. Fluorescent ureteral catheter is visualised clearly via near-infrared light. Fluorescent ureteral catheter can be useful during surgery for T4b rectal cancer.